Sedimentary Dynamics in the Distal Margin Around Isolated Carbonate Platforms of the Northern South China Sea - Chen, Junjin; Wu, Shiguo; Liu, Shiqiao; Chen, Wanli; Qin, Yongpeng; Wan, Xiaoming (Frontiers in Earth Science, 2022)
The South China Sea (SCS) provides an excellent case for studying “source to sink” sedimentary dynamics among the global marginal seas. Analysis of the grain size distribution enables reconstruction of the sediment transport processes and dynamic mechanisms. In this study, based on 232 surface sediment samples acquired in the distal margin of the northern SCS, grain size trend analysis (GSTA) and end-member analysis (EMA) were first applied to the deep-sea environment to reveal the sedimentary dynamics around isolated carbonate platforms. The Zhongsha Atoll and Xisha Archipelagos were the two main sources of gravity flows in the study area. The GSTA results indicate the dominant transport trends that sediments initially originated from the Zhongsha Atoll and Xisha Archipelagos, dispersed in surrounding areas, and eventually formed a deposition center in the Zhongsha Trough. Furthermore, the sediment transport trends in the northern, eastern, and southern boundaries of the study area bounded by the oceanic basin were driven by deep circulation with seasonal variations. The grain size distributions were unmixed into five end-members, with dominant modes of 0.62, 1.89, 3.31, 7.14, and 10.17 Ф, corresponding to coarse sand, medium sand, fine sand, fine silt, and clay, respectively. Gravity flows and deep circulation have a significant impact on the distribution of EMs in the study area. The contents of EM1, EM2, and EM3 decreased while EM4 and EM5 contents increased outward from the ZA to deep-sea areas. Sediments with coarse grains are primarily retained in the ZA, and sediments with fine grains can be transported by gravity flows from platforms to deep-sea areas and removed by deep currents. The sediment transport trends were consistent with the results of sediment sources, seafloor topography, and current observations. These findings indicate that the GSTA is applicable in deep-sea areas.